2019
DOI: 10.1097/sap.0000000000001937
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Nasal Reconstruction After Mohs Surgery

Abstract: Introduction Nasal reconstruction after oncologic resection often constitutes a technically demanding task. The aim of this study was to investigate our experience with nasal reconstruction after Mohs micrographic surgery using the following 3 well-established, versatile, and reliable techniques: the bilobed flap, nasolabial flap, and forehead flap. Methods A single-surgeon retrospective chart review of all patients undergone a bilobed, nasolabial, or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Surgical site infection (SSI) after interpolated flap repair occurred in 4.14% (7/169, 95% CI: 2.02%-9.82%) of patients after flap placement and 2.96% (5/169, 95% CI: 1.27%-6.74%) of patients after flap takedown. Retrospectives studies from single centers 9,10,14,16,17 and a claims database study 13 have reported similar rates of SSI, ranging from 1% to 5.9% after interpolated flap repair. Of note, 76% and 52% of patients in this prospective cohort received prophylactic antibiotics at flap placement and flap takedown, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Surgical site infection (SSI) after interpolated flap repair occurred in 4.14% (7/169, 95% CI: 2.02%-9.82%) of patients after flap placement and 2.96% (5/169, 95% CI: 1.27%-6.74%) of patients after flap takedown. Retrospectives studies from single centers 9,10,14,16,17 and a claims database study 13 have reported similar rates of SSI, ranging from 1% to 5.9% after interpolated flap repair. Of note, 76% and 52% of patients in this prospective cohort received prophylactic antibiotics at flap placement and flap takedown, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…The donor scar is well hidden to the nasolabial fold. 5 However, the main drawback of the flap is the frequent requirement of a second-stage surgery; even when it is transferred in a subcutaneous island flap fashion. The nasolabial perforator flap overcomes this disadvantage and provides closure in a single stage.…”
Section: Discussionmentioning
confidence: 99%
“…Similar propeller flap articles describe reconstruction of difficult medial canthal defects, alar defects, and lateral nasal defects using various propeller flaps based on supratrochlear arteries, facial artery perforators, and central arteries. [3][4][5][6][7] The common unifying theme of all these reconstruction options is that they provide definitive coverage in one stage rather than multiple stages. 8 I applaud the authors for adding to the literature in a topic that has been one of the oldest and best-studied topics in Plastic Surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the modified rhomboid flap adjacent to the defect of the nasal sidewall is often used to repair small defects of skin soft tissues because of its proximity to the defect, and its skin color and texture similar to those of the defect. 7 A few scholars have also used skin graft to reconstruct the small defects on the nasal FIGURE 1. A 34-year-old woman with nasal sidewall tumor (diameter approximately of 7 mm) was excised and underwent the natural tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%